Sources, fluxes, and behaviors of fluorescent dissolved organic matter (FDOM) in the Nakdong River Estuary, Korea - S.-A. Lee; G. Kim (Biogeosciences, 2018)
We monitored seasonal variations in dissolved organic carbon (DOC), the stable carbon isotope of DOC (δ13C-DOC), and fluorescent dissolved organic matter (FDOM) in water samples from a fixed station in the Nakdong River Estuary, Korea. Sampling was performed every hour during spring tide once a month from October 2014 to August 2015. The concentrations of DOC and humic-like FDOM showed significant negative correlations against salinity (r2 =  0.42–0.98, p < 0.0001), indicating that the river-originated DOM components were the major source and behave conservatively in the estuarine mixing zone. The extrapolated δ13C-DOC values (−27.5 to −24.5 ‰) in fresh water confirm that both components are mainly of terrestrial origin. The slopes of humic-like FDOM against salinity were 60–80 % higher in the summer and fall due to higher terrestrial production of humic-like FDOM. The slopes of protein-like FDOM against salinity, however, were 70–80 % higher in spring due to higher biological production in river water. Our results suggest that there are large seasonal changes in riverine fluxes of humic- and protein-like FDOM to the ocean.